# If f(x) = 2x - 9, find f(p) and f(x + h).

### 1 Answer | Add Yours

and `p` is the same as or

Multiply the exponent of (in this case 1) by the co-efficient of and then subtract 1 from the exponent (ie 1-1=0). As now has a zero power or exponent, it falls away.

`therefore f'(x) = 2 times 1 x ^(1-1)= 2x^0```

`therefore f'(x) = p = 2`

Using first principles to verify this answer:

Note we now have** (x+h) - (2x +2h -9)**

Note how the symbol has changed (-9 becomes +9). Now simplify:

`therefore f'(x) = p = 2`

We have from the formula and in this case:

Please note that p = f ' (x) and therefore the question should be continued as follows:

f' (x) = p = 2

`therefore f(p) = f(2) `

Therefore f(p) = 2 (2)-9 = -5

**Ans:**

**f(p)= -5 **

**Sources:**